Counselling in speech-language pathology: Self-efficacy, clinical competencies, and professional development needs in Croatia. - Olujić Tomazin, Marina; Leko Krhen, Ana; Hrastinski, Iva (International Journal of Speech-Language Pathology, 2026)
Purpose: This study investigated counselling practices among speech-language pathologists in Croatia, examining the frequency and timing of counselling, perceived efficacy of counselling skills and clinical competence, attitudes towards speech-language pathologist counselling, and relationships between counselling skills and clinical competencies. Method: Using a cross-sectional design, a total of 113 speech-language pathologists completed an online survey consisting of demographic information, questions about counselling attitudes, the Self-Efficacy Measurement Tool for Counselling in Speech-Language Pathology questionnaire, and a clinical competencies questionnaire. Data were analysed using non-parametric statistics and multiple regression analysis. Result: Despite rating their counselling skills highly, the majority of participants expressed the need for additional counselling training. They expressed the strongest confidence in exploration and action skills but lower confidence in emotional support and insight skills. Counselling skills strongly correlated with general clinical competencies. Emotional support, session management, and action skills explained 62% of the variance in general clinical competencies. Speech-language pathologists with additional counselling training and longer professional experience demonstrated higher self-efficacy in both counselling and clinical skills. Conclusion: The findings highlight the essential role of counselling in speech-language pathology practice, despite the lack of formal training of Croatian professionals. Results suggest a need for mandatory counselling courses in graduate speech-language pathology programmes.